Code generation, analysis tools, and testing for quality - Queiros, Ricardo Alexandre Peixoto de 1975-; Simoes, Alberto 1978-; Pinto, Mario Teixeira 1967- (IGI Global, 2019)
"This book shares new approaches and methodologies for code generation, edition, analysis and testing. It also identifies new trends on these topics, from pedagogical strategies to technological approaches"--
Description based on title screen (IGI Global, viewed 12/18/2018)
Keywords: Computer programs / Testing; Computer software / Quality control; Automatic programming (Computer science)